THU0299 B Cell Compartment and Pharmacodynamics of Belimumab in Systemic Lupus Erythematosus: Early Clinical Efficacy by Depletion of CD27- and Increase of CD27+ B Cells. (15th July 2016) - Quartuccio, L.; De Marchi, G.; Rossi, F.M.; Zuliani, F.; Bond, M.; Picco, L.; Masolini, P.; Rizzolio, F.; De Vita, S.
Abstract : Background: Belimumab, a human anti-BAFF monoclonal antibody that inhibits soluble BAFF, is effective in systemic lupus erythematosus (SLE), and leads to a partial B cell depletion. However, which subset of B cells may be the main therapeutic target of belimumab in SLE is still unclear. Objectives: Primary objective of this study was to evaluate the effect of belimumab on the expression of BAFF receptor (BAFFR) on B cells through 12 months of belimumab treatment in SLE, and to correlate BAFFR expression with changes in B cell subsets. Methods: Twelve consecutive patients with SLE (all female, age 44±7, 8 yrs, 12, 6±5, 4 yrs of disease duration) undergoing belimumab therapy were studied. All patients received at least two immunosuppressors before belimumab. All patients were taking glucocorticoids at baseline [median (range): 7, 5 (0–40) mg/day of prednisone or equivalent)], and 11/12 also at least one immunosuppressor. Median SLEDAI-2k score at baseline was 8, 5 (range 8–15). Samples were collected and analysed at baseline (T0), month +3 (T3), +6 (T6), +9 (T9) and +12 (T12) for clinical and biological parameters. B cells subsets were characterized by multiparametric flowcytometry on a BD FACSCanto flowcytometer. The expression of BAFFR was also analysed as Mean Fluorescence Intensity (MFI). Parametric or non-parametric tests were used, as appropriate based on variable distribution. Data is reported as mean±standard error. Results: A transient statistically significant increase of BAFFR MFI was observed from T0 to T3 (p=0, 004) and from T0 to T6 (p=0, 066) with a subsequent decrease until T12 (table 1 ). Interestingly, this course was similar to that observed in CD19+CD27+ cell subset (table 1 ), that showed a transient significant increase at T3 (p=0, 014) and T6 (p=0, 025) in 9/12 patients, with a subsequent slightly significant decrease from T6 to T12 (p=0, 05) in all patients. Globally, a decrease of CD19+ cells was observed from T0 to T12 (p=0, 19, table 1 ). This course is consistent with that observed in the CD27- B cell subset, that showed a decrease from T0 to T3 (p=0, 14) and from T0 to T6 (p=0, 14), and the decrease was persistent from T6 to T12 (p=0, 6). SLEDAI-2k score decreased from T0 to T3 (p=0, 007), to T6 (p=0, 003) and to T12 (p=0, 03) (table 1 ). Conclusions: BAFF depletion differently acts on B cell subsets, CD19+27+ subset being able to increase BAFFR and transiently expand themselves, while CD19+27- being more sensitive to BAFF deprivation, and faster decreasing. Thus, early clinical response may be related to the changes in the CD27+/CD27- B cell ratio. Disclosure of Interest: None declared